Windfall research and monitoring in the High Tatra Mts., objectives, principles, methods, and current status - FLEISCHER, Peter (Contributions to Geophysics and Geodesy, 2008)
The frequency of heavy windstorms increase in Europe is explained as a possible consequence of the wider global changes. More often, and more intensively, the valuable forest biotopes and protective forest are damaged. Affected sites loose biodiversity, climatic, hydrologic and landscape protection functions, and elevated CO2 is released into the atmosphere. A windstorm on November 19, 2004 in the High Tatra Mts. downed 12.000 ha comprising the wood volume of 2.3 mil m3. One of the largest windfall in history of central Europe initiated an extensive international ecological research. Research on climate, soil and hydrological properties, vegetation, fauna and micro organisms is conducted at fixed research sites. Research focuses on temporal and spatial changes of selected indicators. In the summer 2005, three principal research sites were equipped with eddy covariance towers. Sensors for high rate data record (microclimate, CO2 and water vapour) were installed 5 m above the vegetation. EXT site represents windfall with removed wood and consequent reforestation. NEX site was left without any management; all wood remained on site, and reforestation is not planned. REF site serves as a reference stand. Later, after a large fire which hit 250 ha in the windfall area, FIR site was established. Each site is approximately 100 ha large. Research localities were established at sites with comparable site conditions in the Lariceto-Piceetum forest community. Practical application of the research is the rehabilitation and management of the damaged forest for higher ecological resilience in the future. This paper presents principal methodological approaches needed for an extensive cooperative work of more than 20 institutions from 5 countries, and it summarizes the preliminary results.